A European social semester? The European pillar of social rights in practice - Björn Hacker (European Trade Union Institute (ETUI), 2019)
Following its proclamation in 2017, the European Pillar of Social Rights was used by the Commission for the first time in the 2017/18 European Semester. However, much of the potential of its Social Scoreboard to spotlight social shortcomings in the EU remains untapped. Member States are showing reservations, and budget and competitiveness goals continue to have priority over social goals. The best chance for the latter to find their way into the reform recommendations is when they are seen to be compatible with economic coordination goals. For the Pillar to gain a "social Triple-A" (Jean-Claude Juncker), its goals need to have a more binding character and a greater focus needs to be put on coordinating social policy.
Keywords: 330; EU social policy; EU policy; EU-Sozialpolitik; EU-Politik